Laparoscopic Management of Ectopic Pregnancy (Journal of Fatima Jinnah Medical University, 2018)
Background: Laparoscopic management of gynaecological conditions is gaining popularity due to reduced morbidity and shorter hospital stay as well as for better cosmetic outcomes than open surgery. Although laparoscopic intervention is not a new technique for management of ectopic pregnancy in advanced countries; it is still not as common in Pakistan.Methods: All cases of ectopic pregnancy presenting at Hameed Latif Hospital from 1st Jan 2015 to 31st Jan 2016 were enrolled in this study. Brief history and clinical findings were noted. Trans-vaginal ultrasound and relevant laboratory tests were performed and patients were managed with laparoscopic approach. Findings on laparoscopy were noted and appropriate interventions were undertaken. Any complications identified per-operatively or before discharge from the hospital were also noted. Data were entered in and analysed with SPSS version 21 for windows.Results: Mean age was 29.2 yrs (SD±5.29), 22(75.9%) patients did not have any past surgical history while other 7 (24.1%) had LSCS previously. Lower abdominal pain was the most frequent presenting symptom found in 27 (93.1%) patients. Mean systolic BP was 108mmHg (SD±11.67) with a range of 80 to 130 mmHg. Abdominal tenderness was present on abdominal examination in 20(69%) patients. Laparoscopic surgery was an emergency procedure in 23(79%) cases and elective in the rest (21%). Salpingectomy was the most common procedure performed in 14 (48.3%) patients; other procedures included salpingostomy, milking and others. Blood transfusion was required in 11 (37.9%) patients and there were no post-operative complications. No patient required laparotomy and in all patients diagnosis was found to be correct.Conclusion: Laparoscopic management of ectopic pregnancy is a safe technique with low morbidity rates.
Keywords: Amenorrhea LaparoscopyEctopic pregnancy Salpingectomy